THE SOCIOLOGICAL TRANSFORMATION OF THE TEACHING PROFESSION (Third Sector Social Economic Review, 2025)
The aim of the study is to examine the sociological transformation of the teaching profession by exploring how various social, political and economic factors have shaped the role and status of teachers over time. Traditionally seen as a noble profession, teaching has undergone significant changes, especially with the rise of global education systems, technological advances and changing societal expectations. This study uses both qualitative and quantitative methods to analyse historical changes in teaching practices, teachers' professional identities and the challenges they face in contemporary society. In particular, the study focuses on the impact of neoliberal policies that have altered teachers' autonomy and professional freedom, and the increasing pressure of standardised testing. Data were collected through questionnaires with teachers, interviews with education experts and analyses of education policy documents from many countries. The findings reveal a trend away from professionalisation in many regions where teachers' roles are seen as technicians of standardised curricula rather than intellectual leaders. It also identifies key factors contributing to this change, such as the increasing influence of corporate-oriented educational reforms and the devaluation of teaching as a profession. The study concludes with a discussion of implications for future teacher education and policy-making processes and suggests new recommendations.
Keywords: Sociological Transformation; Teaching Profession; Educational Policies; Neoliberalism; Professional Autonomy